Psychosocial perspective on the integration of individuals deprived of liberty: a lexicometric analysis - Paula Morales Almeida; Pedro Alemán Ramos; Atteneri Medina Montesdeoca (BMC Psychology)
Abstract Objective While some aspects of the prison system are documented, the psychosocial experiences of individuals during incarceration and their reintegration after release remain relatively underexamined and poorly understood by the broader public. Methods This qualitative research explores the perceptions of 16 former people deprived of liberty from Gran Canaria, Spain, focusing on their reintegration process. Semi-structured interviews provided direct and personal insights, analyzed using IRAMuTeQ software to identify key themes. Two main subcorpora emerged: one addressing the experiences within the penitentiary system and the other focusing on the challenges post-release. Results Results revealed significant barriers, such as limited resources in prison, persistent stigma, and difficulties in securing employment and housing. The role of the Social Educator was identified as critical, providing emotional, educational, and social support during incarceration and facilitating connections with community services post-release. Conclusions These findings emphasize the importance of addressing both psychological and social dimensions to promote successful reintegration and highlight the potential of socio-educational programs to foster resilience, self-efficacy, and social integration.